POLA PENGELOLAAN AGROFORESTRI DUSUNG NEGERI LIANG KECAMATAN TELUK ELPAPUTIH KABUPATEN MALUKU TENGAH - Latara, Rahma; Wattimena, Cornelia; Parera, Evelin (MARSEGU : Jurnal Sains dan Teknologi, 2024)
Dusung Agroforestry Management, Negeri Liang, Central Maluku RegencyDusung Agroforestry Management, Negeri Liang, Central Maluku RegencyThe aim of this research is to determine management patterns and factors that influence the hamlets of Liang Village, Teluk Elpaputih District, Central Maluku Regency. Forests have abundant natural resources that can be utilized, resulting in forest use by communities around the forest area. This use is carried out by the community to meet daily living needs. Community dependence on forests is proven by community activities in managing forests to meet living needs. Agroforestry is expected to optimize the results of sustainable land use which is characterized by no decline in crop production over time. and no environmental pollution. These activities are carried out using management pattern practices in accordance with local economic, social and cultural conditions. The survey method is a research method used to obtain data from certain natural places, but research uses questionnaire tests, structured interviews. The results of the research concluded that the Dusung agroforestry management pattern is a mixed pattern (Random Mixture) with the dominance of long-lived plants, cloves and nutmeg, short-lived plants, namely tubers.